High-strength environment-friendly wood-plastic composite material and preparation method thereof
By using chitosan-based flame retardant compatible agents in wood-plastic composites, the problems of poor mechanical properties and flame retardant properties of existing wood-plastic composites are solved, and high-strength and environmentally friendly wood-plastic composites are achieved, which is suitable for industrial production and reduces the risk of carcinogenicity.
Patent Information
- Application Number
- CN202510149890.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The mechanical properties and flame retardant properties of existing wood-plastic composite materials are poor, and the peroxides used during the preparation process are at risk of carcinogenicity, and the commonly used halogen-free flame retardants are inefficient, which affects the mechanical properties of the materials.
Chitosan-based flame retardant compatible agent is used to blend and extrude with polypropylene powder, plant fiber and white carbon black to form a high-strength environmentally friendly wood-plastic composite material. The chitosan-based flame retardant compatible agent forms an intermediate with flame retardant and compatibility improvement effects through esterification reaction and reaction of phenolic hydroxyl groups with 3-bromopropylene.
It significantly improves the mechanical properties and flame retardant properties of wood-plastic composite materials, is green and environmentally friendly and pollution-free, is suitable for industrial production, and reduces the risk of carcinogenicity.
Smart Images

Figure BDA0005267738950000111 
Figure BDA0005267738950000121 
Figure BDA0005267738950000131
Abstract
Description
[0001] This application is a divisional application with the application date of September 9, 2024, application number 202411255150.7, and the invention name is "A high-strength and environmentally friendly wood-plastic composite material and its preparation method." Technical Field
[0002] The invention relates to the technical field of wood-plastic materials, in particular to a high-strength environmentally friendly wood-plastic composite material and a preparation method thereof. Background Art
[0003] Wood-plastic composites (WPC) are a new type of composite material that has been booming in recent years at home and abroad. They refer to the use of conventional polyolefins (including waste recycled materials) as plastic substrates, adding plant fibers as reinforcing components, and then adding appropriate amounts of specific compatibilizers, antioxidants, lubricants and other processing aids. They are mainly used in building materials, furniture, logistics packaging and other industries. They have the advantages of both wood and plastics and are of great significance in environmental protection and alleviating the scarcity of forest resources. Since plant fibers are polar and hydrophilic substances, while plastics are non-polar and hydrophobic substances, the structures between the two are quite different, and it is difficult to achieve interface compatibility, resulting in poor compatibility between wood materials and non-polar plastic matrices, and easy agglomeration, which strongly affects the dispersion of powdered wood materials in the matrix and the performance of composite materials, and the mechanical properties of the composite materials are low. Therefore, the preparation of a high-strength wood-plastic composite material is a hot topic of current research.
[0004] Due to the presence of high-strength hydrogen bonds in plant fiber molecules, they will gather together when heated and mixed, and are easy to form agglomerates, and are not easy to be evenly dispersed in the plastic matrix, thereby affecting the composite properties of the composite material; currently, the commonly used modification methods include the coupling agent method and the compatibilizer method, but it has been reported that when the coupling agent method is used, because plant fibers such as rice bran are loose porous fillers, when the amount of coupling agent is small, they are easily absorbed by rice bran and the like into their micropores, and it is difficult to form a uniform coating layer on the surface of the rice bran; therefore, the use of conventional coupling agents to treat wood fillers often has little effect, but increases the cost; most of the existing wood-plastic composite materials use, for example, the technical solution disclosed in CN1990599A to achieve cross-linking between the wood-plastic composite matrix by adding peroxide to prepare a high-strength composite material, but the amount and properties of peroxides added during processing are not well controlled, and peroxides are prohibited as product raw materials in many fields, and the risk of carcinogenesis is high.
[0005] In addition, since the main raw materials of wood-plastic composite materials, plant fibers and plastics, are both flammable materials, there are certain safety hazards when they are used, and flame retardant treatment is required; inorganic flame retardants and halogen-containing flame retardants are often used for the flame retardancy of polypropylene and wood; however, halogen-containing flame retardants are harmful to the environment, and halogen-free flame retardancy of materials is highly valued; inorganic flame retardants are inefficient, and in order to make the flame retardant properties of the material meet certain requirements, the filling mass fraction must be as high as 40-60%, which will have a greater impact on the mechanical properties of the material and is difficult to meet the use requirements. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art, provide a high-strength environmentally friendly wood-plastic composite material and a preparation method thereof, solve the problem of poor mechanical properties and flame retardant properties of the existing wood-plastic composite material, be green, environmentally friendly, pollution-free, and suitable for industrial production.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A high-strength environmentally friendly wood-plastic composite material comprises the following components in parts by weight: 100 parts of polypropylene powder, 50-65 parts of plant fiber, 15-20 parts of white carbon black, 3-15 parts of chitosan-based flame retardant compatibilizer, 2-5 parts of lubricant, 1-3 parts of antioxidant and 0.5-2 parts of light stabilizer.
[0009] The preparation method of chitosan-based flame retardant compatibilizer is as follows: under a nitrogen atmosphere, initiators diisopropylbenzene peroxide and N,N-dimethylacetamide are added into a reaction flask, after being stirred evenly, polypropylene powder, styrene, maleic anhydride and chitosan-based phosphorus-containing nitrogen matrix are added, reacting at 55-70° C. for 8-16 hours, filtering, washing with petroleum ether, and drying to obtain the chitosan-based flame retardant compatibilizer.
[0010] Preferably, the plant fiber is any one of wood powder, bamboo powder, rice husk powder, flax fiber or ramie fiber.
[0011] Preferably, the lubricant is any one of calcium stearate, polyethylene wax or polypropylene wax.
[0012] Preferably, the ratio of the initiator diisopropylbenzene peroxide, N,N-dimethylacetamide, polypropylene, styrene, maleic anhydride, and chitosan-based phosphorus-containing nitrile matrix is (0.02-0.05) g: (45-60) mL: 1 g: (0.35-0.5) g: (0.2-0.4) g: (0.05-0.15) g.
[0013] Preferably, the preparation method of the chitosan-based phosphorus-containing nitrene intermediate is:
[0014] Step (1), under nitrogen atmosphere, add 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and ethanol into a reaction flask, stir to dissolve, add chitosan, react at 65-80° C. for 12-24 h, filter while hot, wash with ethanol, and dry to obtain chitosan-based Schiff base.
[0015] Step (2), under nitrogen atmosphere, add DOPO and N,N-dimethylformamide into a reaction flask, stir evenly, add chitosan-based Schiff base, react at 50-70° C. for 5-12 h, cool to room temperature, filter, wash with ethanol, and dry to obtain a diphenol chitosan-based DOPO intermediate.
[0016] Step (3), under nitrogen atmosphere, add diphenol chitosan-based DOPO intermediate and tetrahydrofuran into a reaction flask, stir evenly, add 3-bromopropylene and sodium hydride, react at 40-60° C. for 8-16 h, cool and filter, wash with deionized water, and dry to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0017] Preferably, in step (1), the ratio of 2,6-dihydroxynaphthalene-1,5-dicarbaldehyde, ethanol and chitosan is 1 g: (10-20) mL: (4.5-6.2) g.
[0018] Preferably, in step (2), the ratio of DOPO, N,N-dimethylformamide, and chitosan-based Schiff base is 1 g: (15-30) mL: (5.2-7.5) g.
[0019] Preferably, in step (3), the ratio of diphenol chitosan-based DOPO intermediate, tetrahydrofuran, 3-bromopropylene, and sodium hydride is 1 g: (20-30) mL: (0.1-0.2) g: (0.03-0.05) g.
[0020] Preferably, the preparation method is: adding polypropylene powder, plant fiber, white carbon black, chitosan-based flame retardant compatibilizer, lubricant, antioxidant and light stabilizer into a high-speed mixer and stirring evenly, mixing at a temperature of 100-120°C and a speed of 250-300r / min for 10-20min, cooling and discharging to obtain a premix, and putting the premix into a parallel twin-screw machine for granulation and extrusion, the granulation temperature is 160-185°C, the screw speed is 300-350r / min; the extrusion temperature is controlled at 170-190°C, the screw speed is 10-15r / min, and then placing it in a flat vulcanizer for vulcanization to obtain a high-strength environmentally friendly wood-plastic composite material.
[0021] Preferably, the vulcanization temperature is 180-200° C. and the vulcanization pressure is 8-15 MPa.
[0022] By adopting the above technical solution, the beneficial effects of the present invention are:
[0023] The invention firstly carries out an amination reaction on the aldehyde group of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and the amino group of chitosan to obtain a chitosan-based Schiff base containing a C=N structure, then uses the chitosan-based Schiff base to carry out a Michael addition reaction with DOPO to obtain a diphenol chitosan-based DOPO intermediate, then uses the phenolic hydroxyl group in the structure to react with 3-bromopropylene under the action of sodium hydride to obtain a chitosan-based phosphorus-containing nitrogen-containing intermediate, then reacts with polypropylene powder, maleic anhydride and the like to obtain a chitosan-based flame retardant compatibilizer, and finally blends and extrude with polypropylene powder, plant fiber, white carbon black and the like to obtain a high-strength environmentally friendly wood-plastic composite material.
[0024] Chitosan is a rich, renewable green resource with the advantages of being green, environmentally friendly and renewable. Its structure is rich in hydroxyl, carbon and nitrogen elements, and can produce non-toxic and non-flammable gases such as N2, CO2, NH3, H2O, etc. when burned, which can dilute the concentration of oxygen and combustible gases, thereby playing a flame retardant role. On the other hand, the DOPO fragment in the chitosan-based flame retardant compatibilizer can produce phosphorus-containing free radicals, which can capture the free radicals produced during the combustion process and interrupt the combustion chain reaction. At the same time, it can produce synergistic flame retardancy with the nitrogen element in chitosan, forming a carbon protective layer during combustion to inhibit the combustion of the composite material. Its structure contains a large number of rigid naphthalene rings and phosphaphenanthrene rings, which can hinder the movement of molecular chain segments, which is beneficial to improving the thermal properties and fire performance index of the composite material, and has a good flame retardant effect on polypropylene-based wood-plastic composite materials.
[0025] One end of the chitosan-based flame retardant compatibilizer molecule is an anhydride group. During the high-temperature shearing process of the composite material, the anhydride group produces an esterification reaction with a large number of hydroxyl groups on the surface of the plant fiber and white carbon black. The other end is polypropylene, which is entangled with the matrix PP molecules of the composite material. Therefore, the compatibilizer plays a role of a link, connecting the plant fiber and white carbon black at one end and the matrix PP at the other end, so that the compatibility between the polar plant fiber, white carbon black and non-polar PP is improved; the introduction of the chitosan-based flame retardant compatibilizer can promote the dispersion of polypropylene and plant fibers, so that a uniform and refined sea-island structure is formed between the two, forming a cross-linked area similar to an interpenetrating network structure, thereby greatly improving the mechanical properties of the wood-plastic composite material. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention is further described below by specific embodiments. It should be understood that the specific embodiments described herein are only used to help understand the present invention and are not intended to be used for specific limitations of the present invention. Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.
[0027] Chitosan, degree of deacetylation ≧95%, viscosity 100-200 Pa·s, McLean Biochemical Technology Co., Ltd.
[0028] 2,6-Dihydroxynaphthalene-1,5-dicarbaldehyde, CAS number is 7235-47-4.
[0029] DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide), CAS number is 35948-25-5.
[0030] Example 1
[0031] (1) Under a nitrogen atmosphere, 40 g of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 600 mL of ethanol were added to a reaction flask, stirred to dissolve, and then 220 g of chitosan was added. The mixture was reacted at 75° C. for 16 h, filtered while hot, washed with ethanol, and dried to obtain a chitosan-based Schiff base.
[0032] (2) Under nitrogen atmosphere, 35 g of DOPO and 700 mL of N,N-dimethylformamide were added to a reaction flask, stirred evenly, and then 231 g of chitosan-based Schiff base was added. The mixture was reacted at 60 °C for 10 h, cooled to room temperature, filtered, washed with ethanol, and dried to obtain a diphenol chitosan-based DOPO intermediate.
[0033] (3) Under nitrogen atmosphere, 30 g of diphenol chitosan-based DOPO intermediate and 750 mL of tetrahydrofuran were added to a reaction flask. After stirring, 4.5 g of 3-bromopropylene and 0.04 g of sodium hydride were added. The mixture was reacted at 50 °C for 12 h, cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0034] (4) Under nitrogen atmosphere, 1 g of initiator diisopropylbenzene peroxide and 1300 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring evenly, 25 g of polypropylene powder, 10.5 g of styrene, 8 g of maleic anhydride and 2.5 g of chitosan-based phosphorus-containing nitrogen matrix were added, and the mixture was reacted at 65 °C for 12 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based flame retardant compatibilizer.
[0035] (5) 100 g of polypropylene powder, 55 g of wood powder, 16 g of white carbon black, 3 g of chitosan-based flame retardant compatibilizer, 4 g of calcium stearate, 2 g of antioxidant 168 and 1.5 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 110° C. and a rotation speed of 260 r / min for 15 min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 170° C. and the screw speed was 320 r / min. The extrusion temperature was controlled at 180° C. and the screw speed was 12 r / min. Then, the premix was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 190° C. and the vulcanization pressure was 10 MPa to obtain a high-strength environmentally friendly wood-plastic composite material.
[0036] Example 2
[0037] (1) Under a nitrogen atmosphere, 75 g of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 750 mL of ethanol were added to a reaction flask, and after stirring to dissolve, 337.5 g of chitosan was added, and the mixture was reacted at 80° C. for 12 h. The mixture was filtered while hot, washed with ethanol, and dried to obtain a chitosan-based Schiff base.
[0038] (2) Under nitrogen atmosphere, 70 g of DOPO and 1050 mL of N,N-dimethylformamide were added to a reaction flask, stirred evenly, and then 364 g of chitosan-based Schiff base was added. The mixture was reacted at 70 °C for 5 h, cooled to room temperature, filtered, washed with ethanol, and dried to obtain a diphenol chitosan-based DOPO intermediate.
[0039] (3) Under nitrogen atmosphere, 65 g of diphenol chitosan-based DOPO intermediate and 1300 mL of tetrahydrofuran were added to a reaction flask. After stirring, 6.5 g of 3-bromopropylene and 1.95 g of sodium hydride were added. The mixture was reacted at 60° C. for 8 h, cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0040] (4) Under nitrogen atmosphere, 1.2 g of initiator diisopropylbenzene peroxide and 2700 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring evenly, 60 g of polypropylene powder, 21 g of styrene, 12 g of maleic anhydride and 3 g of chitosan-based phosphorus-containing nitrogen matrix were added, and the mixture was reacted at 70 ° C for 8 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based flame retardant compatibilizer.
[0041] (5) 100 g of polypropylene powder, 50 g of bamboo powder, 15 g of white carbon black, 6 g of chitosan-based flame retardant compatibilizer, 3 g of polyethylene wax, 1 g of antioxidant 168 and 0.5 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. The mixture was mixed at a temperature of 120° C. and a speed of 300 r / min for 10 min and then cooled to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 185° C. and the screw speed was 350 r / min. The extrusion temperature was controlled at 190° C. and the screw speed was 15 r / min. The mixture was then placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 200° C. and the vulcanization pressure was 15 MPa. A high-strength environmentally friendly wood-plastic composite material was obtained.
[0042] Example 3
[0043] (1) Under a nitrogen atmosphere, 30 g of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 600 mL of ethanol were added to a reaction flask, and after stirring to dissolve, 186 g of chitosan was added, and the mixture was reacted at 65° C. for 24 h. The mixture was filtered while hot, washed with ethanol, and dried to obtain a chitosan-based Schiff base.
[0044] (2) Under nitrogen atmosphere, 25 g of DOPO and 750 mL of N,N-dimethylformamide were added to a reaction flask, stirred evenly, and then 187.5 g of chitosan-based Schiff base was added. The mixture was reacted at 50 °C for 12 h, cooled to room temperature, filtered, washed with ethanol, and dried to obtain a diphenol chitosan-based DOPO intermediate.
[0045] (3) Under nitrogen atmosphere, 20 g of diphenol chitosan-based DOPO intermediate and 600 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 4 g of 3-bromopropylene and 1 g of sodium hydride were added. The mixture was reacted at 40° C. for 16 h, cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0046] (4) Under nitrogen atmosphere, 0.75 g of initiator diisopropylbenzene peroxide and 900 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring evenly, 15 g of polypropylene powder, 7.5 g of styrene, 6 g of maleic anhydride and 2.25 g of chitosan-based phosphorus-containing nitrogen matrix were added, and the mixture was reacted at 55 °C for 16 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based flame retardant compatibilizer.
[0047] (5) 100 g of polypropylene powder, 65 g of rice husk powder, 20 g of white carbon black, 9 g of chitosan-based flame retardant compatibilizer, 5 g of polypropylene wax, 3 g of antioxidant 168 and 2 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 100° C. and a rotation speed of 250 r / min for 20 min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 160° C. and the screw speed was 300 r / min. The extrusion temperature was controlled at 170° C. and the screw speed was 10 r / min. Then, the premix was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 180° C. and the vulcanization pressure was 8 MPa to obtain a high-strength environmentally friendly wood-plastic composite material.
[0048] Example 4
[0049] (1) Under a nitrogen atmosphere, 45 g of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 720 mL of ethanol were added to a reaction flask, stirred to dissolve, and then 235 g of chitosan was added. The mixture was reacted at 75° C. for 12 h, filtered while hot, washed with ethanol, and dried to obtain a chitosan-based Schiff base.
[0050] (2) Under nitrogen atmosphere, 42 g of DOPO and 760 mL of N,N-dimethylformamide were added to a reaction flask, stirred evenly, and then 275 g of chitosan-based Schiff base was added. The mixture was reacted at 65 °C for 10 h, cooled to room temperature, filtered, washed with ethanol, and dried to obtain a diphenol chitosan-based DOPO intermediate.
[0051] (3) Under nitrogen atmosphere, 40 g of diphenol chitosan-based DOPO intermediate and 880 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 2 g of 3-bromopropylene and 1.44 g of sodium hydride were added, and the mixture was reacted at 55° C. for 16 h. The mixture was cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0052] (4) Under nitrogen atmosphere, 1.12 g of initiator diisopropylbenzene peroxide and 1925 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring evenly, 35 g of polypropylene powder, 14.7 g of styrene, 10.5 g of maleic anhydride and 2.8 g of chitosan-based phosphorus-containing nitrogen matrix were added, and the mixture was reacted at 65 ° C for 12 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based flame retardant compatibilizer.
[0053] (5) 100 g of polypropylene powder, 60 g of flax fiber, 18 g of white carbon black, 12 g of chitosan-based flame retardant compatibilizer, 4 g of calcium stearate, 2.5 g of antioxidant 168 and 1 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 115° C. and a rotation speed of 260 r / min for 12 min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 175° C. and the screw speed was 300 / min; the extrusion temperature was controlled at 185° C. and the screw speed was 12 r / min. Then, the premix was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 200° C. and the vulcanization pressure was 12 MPa to obtain a high-strength environmentally friendly wood-plastic composite material.
[0054] Example 5
[0055] (1) Under a nitrogen atmosphere, 20 g of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and 360 mL of ethanol were added to a reaction flask, and after stirring to dissolve, 105 g of chitosan was added, and the mixture was reacted at 80° C. for 16 h. The mixture was filtered while hot, washed with ethanol, and dried to obtain a chitosan-based Schiff base.
[0056] (2) Under nitrogen atmosphere, 18 g of DOPO and 450 mL of N,N-dimethylformamide were added to a reaction flask, and after stirring, 115 g of chitosan-based Schiff base was added. The mixture was reacted at 70 °C for 8 h, cooled to room temperature, filtered, washed with ethanol, and dried to obtain a diphenol chitosan-based DOPO intermediate.
[0057] (3) Under nitrogen atmosphere, 12 g of diphenol chitosan-based DOPO intermediate and 300 mL of tetrahydrofuran were added to a reaction flask. After stirring evenly, 1.8 g of 3-bromopropylene and 0.42 g of sodium hydride were added. The mixture was reacted at 50 °C for 12 h, cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based phosphorus-containing nitrogen olefin intermediate.
[0058] (4) Under nitrogen atmosphere, 0.25 g of initiator diisopropylbenzene peroxide and 500 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring evenly, 10 g of polypropylene powder, 4.2 g of styrene, 2.3 g of maleic anhydride and 1.2 g of chitosan-based phosphorus-containing nitrogen matrix were added, and the mixture was reacted at 70 ° C for 15 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based flame retardant compatibilizer.
[0059] (5) 100 g of polypropylene powder, 60 g of ramie fiber, 20 g of white carbon black, 15 g of chitosan-based flame retardant compatibilizer, 3 g of polyethylene wax, 2 g of antioxidant 168 and 2 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. The mixture was mixed at a temperature of 105° C. and a rotation speed of 300 r / min for 20 min and then cooled to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 180° C. and the screw speed was 320 r / min. The extrusion temperature was controlled at 185° C. and the screw speed was 12 r / min. The mixture was then placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 185° C. and the vulcanization pressure was 15 MPa. A high-strength environmentally friendly wood-plastic composite material was obtained.
[0060] Comparative Example 1
[0061] (1) Under nitrogen atmosphere, 30 g of chitosan-based Schiff base (prepared in Example 1) and 750 mL of tetrahydrofuran were added to a reaction flask, and after stirring, 4.5 g of 3-bromopropylene and 0.04 g of sodium hydride were added, and the mixture was reacted at 50° C. for 12 h, cooled and filtered, washed with deionized water, and dried to obtain a chitosan-based alkenyl intermediate.
[0062] (2) Under nitrogen atmosphere, 1 g of initiator diisopropylbenzene peroxide and 1300 mL of N,N-dimethylacetamide were added to the reaction flask, and after stirring, 25 g of polypropylene powder, 10.5 g of styrene, 8 g of maleic anhydride and 2.5 g of chitosan-based alkenyl intermediate were added, and the mixture was reacted at 65 °C for 12 h. The mixture was filtered, washed with petroleum ether, and dried to obtain a chitosan-based compatibilizer.
[0063] (3) 100 g of polypropylene powder, 55 g of wood powder, 16 g of white carbon black, 3 g of chitosan-based compatibilizer, 4 g of calcium stearate, 2 g of antioxidant 168 and 1.5 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 110° C. and a rotation speed of 260 r / min for 15 min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 170° C. and the screw speed was 320 r / min. The extrusion temperature was controlled at 180° C. and the screw speed was 12 r / min. Then, the premix was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 190° C. and the vulcanization pressure was 10 MPa to obtain a wood-plastic composite material.
[0064] Comparative Example 2
[0065] (1) Under nitrogen atmosphere, 1 g of initiator diisopropylbenzene peroxide and 1300 mL of N,N-dimethylacetamide were added to a reaction flask, stirred evenly, and then 25 g of polypropylene powder, 10.5 g of styrene, and 8 g of maleic anhydride were added. The mixture was reacted at 65 °C for 12 h, filtered, washed with petroleum ether, and dried to obtain a compatibilizer.
[0066] (2) 100 g of polypropylene powder, 55 g of wood powder, 16 g of white carbon black, 3 g of compatibilizer, 4 g of calcium stearate, 2 g of antioxidant 168 and 1.5 g of light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 110° C. and a rotation speed of 260 r / min for 15 min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 170° C. and the screw speed was 320 r / min. The extrusion temperature was controlled at 180° C. and the screw speed was 12 r / min. Then, the premix was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 190° C. and the vulcanization pressure was 10 MPa to obtain a wood-plastic composite material.
[0067] Comparative Example 3
[0068] 100g polypropylene powder, 55g wood powder, 16g white carbon black, 4g calcium stearate, 2g antioxidant 168 and 1.5g light stabilizer 622 were added to a high-speed mixer and stirred evenly. After high-speed mixing at a temperature of 110°C and a rotation speed of 260r / min for 15min, the material was cooled and discharged to obtain a premix. The premix was put into a parallel twin-screw machine for granulation and extrusion. The granulation temperature was 170°C and the screw speed was 320r / min; the extrusion temperature was controlled at 180°C and the screw speed was 12r / min. Then, it was placed in a flat vulcanizer for vulcanization. The vulcanization temperature was 190°C and the vulcanization pressure was 10MPa to obtain a wood-plastic composite material.
[0069] Limiting oxygen index test: According to GB / T 2406.2-2009, an oxygen index meter is used to measure the limiting oxygen index of wood-plastic composite materials.
[0070] Fire performance index test: According to ISO 5660 standard, the combustion performance of wood-plastic composite materials was determined using a cone calorimeter. The sample size was 100mm×100mm×2mm and the horizontal radiation intensity was 35kW / m 2 .
[0071] Table 1 Flame retardant performance test
[0072]
[0073] The limiting oxygen index refers to the volume fraction of oxygen when a polymer can just support its combustion in a mixture of oxygen and nitrogen. It is one of the important parameters used to evaluate the flame retardant properties of flame retardants. It can be seen from the test results in the above table that with the increase of the content of chitosan-based flame retardant compatibilizer, the flame retardant properties of wood-plastic composite materials are gradually enhanced. The limiting oxygen index in Example 5 reaches 31.0%, which belongs to the level of flame-retardant materials. This is because chitosan is rich in hydroxyl, carbon and nitrogen elements, and can produce non-toxic and non-flammable gases such as N2, CO2, NH3, H2O, etc. when burned. etc., which can dilute the concentration of oxygen and combustible gas, thereby playing a flame retardant role; on the other hand, the DOPO fragment in the chitosan-based flame retardant compatibilizer can produce phosphorus-containing free radicals, which can capture the free radicals produced during the combustion process, interrupting the combustion chain reaction, and at the same time can produce synergistic flame retardancy with the nitrogen element in chitosan, forming a carbon protective layer during combustion, inhibiting the combustion of the composite material, and the chitosan-based flame retardant compatibilizer structure contains a large number of rigid naphthalene rings and phosphaphenanthrene rings, which have the effect of hindering the movement of molecular chain segments, which is beneficial to improving the thermal properties of the composite material.
[0074] The fire performance index is the ratio of the ignition time to the maximum heat release rate, which is used to predict whether the material will burn after ignition in a fire. The smaller the fire performance index, the faster the combustion, the greater the danger of the fire, and the worse the flame retardant performance of the composite material. From the test results in the above table, it can be seen that after adding the chitosan-based flame retardant compatibilizer, the fire performance index of the composite material is significantly improved, indicating that the chitosan-based flame retardant compatibilizer has a good flame retardant effect on polypropylene-based wood-plastic composite materials.
[0075] Comparative Example 1 does not contain DOPO fragments and only uses chitosan, so the flame retardant effect is limited; Comparative Examples 2 and 3 do not contain any flame retardant elements and do not have flame retardant properties, but Comparative Example 2 contains a compatibilizer, which can improve the densification of the composite material to a certain extent and play a certain role in flame retardancy, but the effect is limited.
[0076] Tensile performance test: The test was carried out at room temperature according to GB / T 1040-2006 standard, with a tensile rate of 20 mm / min.
[0077] Impact performance test: The test is carried out in accordance with GB / T 1843-2008 standard, and the specimen is a non-notched specimen.
[0078] Bending performance test: Tested in accordance with GB / T 9341-2008.
[0079] Table 2 Mechanical properties test
[0080]
[0081]
[0082] From the test results in the above table, it can be seen that with the increase of the content of chitosan-based flame retardant compatibilizer, the mechanical properties of the wood-plastic composite material are gradually enhanced, wherein the tensile strength in Example 4 is 38.0 MPa, and the impact strength is 31.6 kJ / m 2 The bending modulus is 4.49GPa. This is because one end of the chitosan-based flame retardant compatibilizer molecule is an anhydride group. During the high-temperature shearing process of the composite material, the anhydride group produces an esterification reaction with the hydroxyl groups on the surface of the plant fiber and white carbon black, and the polypropylene at the other end is entangled with the matrix PP molecules of the composite material. Therefore, the compatibilizer plays a role of a link, connecting the plant fiber and white carbon black at one end and the matrix PP at the other end, so that the compatibility between the polar plant fiber, white carbon black and non-polar PP is improved; the introduction of the chitosan-based flame retardant compatibilizer can promote the dispersion of polypropylene and plant fibers, so that a uniform and refined sea-island structure is formed between the two, forming a cross-linked area similar to an interpenetrating network structure, thereby greatly improving the mechanical properties of the wood-plastic composite material.
[0083] Finally, it should be noted that the specific embodiments described herein are merely examples of the spirit of the present invention, and are not intended to limit the implementation methods of the present invention. Those skilled in the art of the present invention may make various modifications or supplements to the described embodiments or replace them in similar ways. It is not necessary and impossible to provide all examples of all implementation methods here, and these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention. It is contrary to the spirit of the present invention to interpret them as any additional limitations.
Claims
1. A high-strength environmentally friendly wood-plastic composite material, characterized in that: The wood-plastic composite material comprises the following components in parts by weight: 100 parts of polyethylene powder, 120-150 parts of plant fiber, 15-20 parts of white carbon black, 3-15 parts of chitosan-based flame retardant compatibilizer, 2-5 parts of lubricant, 1-3 parts of antioxidant and 0.5-2 parts of light stabilizer; The plant fiber is any one of wood powder, bamboo powder, rice husk powder, flax fiber or ramie fiber; The lubricant is any one of calcium stearate, polyethylene wax or polypropylene wax; The preparation method of the chitosan-based flame retardant compatibilizer is as follows: in a nitrogen atmosphere, initiators dicumyl peroxide and N,N-dimethylacetamide are added to a reaction flask, after being stirred evenly, polyethylene powder, styrene, maleic anhydride and chitosan-based phosphorus-containing nitrogen-containing intermediate are added, reacting at 55-70° C. for 8-16 hours, filtering, washing with petroleum ether, and drying to obtain the chitosan-based flame retardant compatibilizer; The ratio of the initiator dicumyl peroxide, N,N-dimethylacetamide, polyethylene, styrene, maleic anhydride, and chitosan-based phosphorus-containing nitrogen-containing intermediate is (0.02-0.05) g: (45-60) mL: 1 g: (0.35-0.5) g: (0.2-0.4) g: (0.05-0.15) g; The preparation method of the chitosan-based phosphorus-containing nitrogen olefin intermediate comprises the following steps: step (1), adding 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde and ethanol to a reaction flask under a nitrogen atmosphere, stirring and dissolving, and then adding chitosan, wherein the ratio of 2,6-dihydroxynaphthalene-1,5-dicarboxaldehyde, ethanol and chitosan in step (1) is 1 g: (10-20) mL: (4.5-6.2) g, reacting at 65-80° C. for 12-24 h, filtering while hot, washing with ethanol, and drying to obtain a chitosan-based Schiff base; Step (2), under nitrogen atmosphere, add DOPO and N,N-dimethylformamide to a reaction flask, stir evenly, add chitosan-based Schiff base, react at 50-70° C. for 5-12 hours, cool to room temperature, filter, wash with ethanol, and dry to obtain a diphenol chitosan-based DOPO intermediate; in the step (2), the ratio of DOPO, N,N-dimethylformamide, and chitosan-based Schiff base is 1 g: (15-30) mL: (5.2-7.5) g; Step (3), under a nitrogen atmosphere, add a diphenol chitosan-based DOPO intermediate and tetrahydrofuran to a reaction flask, stir evenly, add 3-bromopropylene and sodium hydride, react at 40-60° C. for 8-16 hours, cool and filter, wash with deionized water, and dry to obtain a chitosan-based phosphorus-containing nitrogen-containing intermediate; in the step (3), the ratio of the diphenol chitosan-based DOPO intermediate, tetrahydrofuran, 3-bromopropylene, and sodium hydride is 1 g: (20-30) mL: (0.1-0.2) g: (0.03-0.05) g.
2. A method for preparing a high-strength environmentally friendly wood-plastic composite material as claimed in claim 1, characterized in that: The preparation method comprises the following steps: adding polyethylene powder, plant fiber, white carbon black, chitosan-based flame retardant compatibilizer, lubricant, antioxidant and light stabilizer into a high-speed mixer and stirring evenly; mixing at a temperature of 100-120° C. and a rotation speed of 250-300 r / min for 10-20 min, cooling and discharging the mixture to obtain a premix; putting the premix into a parallel twin-screw machine for granulation and extrusion, wherein the granulation temperature is 160-185° C. and the screw rotation speed is 300-350 r / min; the extrusion temperature is controlled at 170-190° C. and the screw rotation speed is 10-15 r / min; and then placing the mixture in a flat vulcanizer for vulcanization to obtain a high-strength environmentally friendly wood-plastic composite material.
3. The method for preparing the high-strength environmentally friendly wood-plastic composite material according to claim 2, characterized in that: The vulcanization temperature is 180-200° C., and the vulcanization pressure is 8-15 MPa.
Citation Information
Patent Citations
Wood-plastic composite material and preparation method thereof
CN1990599A